Implementasi Sistem Keuangan pada Toko Bangunan Batam melalui Microsoft Access - Iskandar Itan; Nobellya Rivanti (Pusat Riset dan Inovasi Nasional, 2026)
Information systems are an important element in the business world that helps businesses increase work efficiency and reduce human error. In practice, many businesses still produce financial reports manually. Manual preparation of financial reports is inefficient and tends to have a higher potential for delays, lateness, or errors in data entry. This makes the financial reports presented inaccurate and unreliable as a basis for making decisions. To address this problem, a community service program was implemented by designing an accounting system using Microsoft Access, which provides various features that can help users in data processing. The method carried out starts with observation, system design, and evaluation by the partner. The result of implementing this program is that the system designed in Microsoft Access successfully accelerated the work process for partners, making the preparation of financial reports more efficient and timely. The financial reports presented also became more accurate and reliable.